Synthesis and Biological Activities of Some Benzimidazoles Derivatives - Hamdan S Al-Ebaisat (Journal of Applied Sciences and Environmental Management)
A set of six novel benzimidazoles compounds were prepared, this includes 5- Nitro-2-phenyl -1-ethylbenzimidazol (5),2-(p-Bromophenyl)-5-nitro-1-ethylbenzimidazol (6), 2- (p- Bromophenyl- 5-nitro-1–cyclopentylbenzimidazol(7),2-(p-Bromophenyl)-5-nitro-1- cyclopentylbenzimidazol (8),5-Amino-2-(p-Bromophenyl)-1-ethylbenzimidazol (9), and 5-Amino- (2- (p- Bromophenyl)- 1- cyclopentylbenzimidazol (10). The chemical structures of these compounds were elucidated using NMR and elemental analysis. The biological activity of these compounds as fungicides was tested against three commercially known fungicides (C. albicans, patient isolate C. glabrata and C. krusei).The biological activity of two compounds was found to be comparable to that of the commercially available fungicides (6 and 9). @JASEM